The Students' Caring Attitude Toward Marine Environment through Integrated Natural Science Learning in SMP Negeri Tanjungpinang - Dios Sarkity; Adam Fernando; Nur Eka Kusuma Hindrasti (Universitas Muhammadiyah Sidoarjo, 2023)
Various marine environment damages were caused by a lack of marine environmental care attitude. This attitude must be instilled from an early age. This study aimed to find out how marine environmental care attitude of students of public junior high schools in Tanjungpinang City through integrated science learning. This research was a quantitative descriptive research in the form of a survey. This research involved 572 public secondary school students in Tanjungpinang City out of a total of 7,974 stundents who were determined using stratified random sampling. Data collection was carried out using a questionnaire. Questions on the questionnaire were based on 4 main indicators which were based on 7 ocean literacy principles and literature review on environtmental care attitude. Data were analyzed descriptively quantitatively using a Likert Scale. The results showed that students' knowledge of the sea was in the good category. Students' attitudes in preserving marine environment and preventing marine environmental damages were in the good category and the contribution of integrated science learning in shaping these attitudes was also in the good category. The students’ attitudes in repairing marine environment damages was in the bad category and the contribution of integrated science learning to this attitude was in the very bad category. This did not indicate the low quality of integrated science learning. During the COVID-19 Pandemic, it was impossible for integrated science learning to be carried out in the marine environment by involving students in activities to repair marine environment damages because of physical interaction restrictions.